2004
DOI: 10.1007/s00392-004-1402-4
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of cardiac dysrhythmias in acute intoxication

Abstract: Cardiac dysrhythmias are common in acute intoxications. However, epidemiological data is rare and restricted to specific substances. From 1995 to 2003 (until September) 91 285 inquiries of physicians and paramedics to a poison center regarding acute intoxications were analyzed revealing 9888 patients (10.8%) suffering from disturbances of the cardiac rhythm. In a first step of the explorative data analysis dysrhythmias were graduated into three categories (I: tachycardia/bradycardia; II: arrhythmia/conduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…In a report on 5,529 cases of individuals intoxicated by recreational drugs and new psychoactive substances in Europe, 69.5% of these individuals went to the hospital by ambulance, 56.9% of whom were medically discharged from the ED; only 35 (0.6%) presented with cardiac arrest ( 23 ). In Germany, a report using poison data from ambulance services found that 10.8% of the 91,285 patients has dysrhythmia, and 111 (0.1%) had cardiac arrest ( 24 ). We could not directly compare our findings with the cardiac arrest survival rate of this study due to the lack of information on survival.…”
Section: Discussionmentioning
confidence: 99%
“…In a report on 5,529 cases of individuals intoxicated by recreational drugs and new psychoactive substances in Europe, 69.5% of these individuals went to the hospital by ambulance, 56.9% of whom were medically discharged from the ED; only 35 (0.6%) presented with cardiac arrest ( 23 ). In Germany, a report using poison data from ambulance services found that 10.8% of the 91,285 patients has dysrhythmia, and 111 (0.1%) had cardiac arrest ( 24 ). We could not directly compare our findings with the cardiac arrest survival rate of this study due to the lack of information on survival.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the largest and most recent study, which systematically researched cardiac dysrhythmias in poisonings by von Mach et al was published in 2004. 3 Although dysrhythmias were reported for sotalol, no fatalities occurred. In our study, we did not advocate to take sotalol exposures lightly.…”
Section: Response To Neuvonen Et Al: Sotalol Unlike the Other Beta-bmentioning
confidence: 97%
“…In diesen Fäl-len ist die Indikationen zur Antidottherapie mit Azetylcystein großzügig zu stellen[6,12].-Kardiale Symptomatik: b 2 -Sympathomimetika, ImidazolinDerivate, Digitalis-Glykoside, b-Blocker und Theophyllin. Diese Substanzgruppen führen zu tachykarden (b 2 -Sympathomimetika, Imidazolin-Derivate, Theophyllin) oder bradykarden (Digitalis-Glykoside, b-Blocker) Herzrhythmusstörungen[11].…”
unclassified